Unrepaired DNA damage facilitates elimination of uniparental chromosomes in interspecific hybrid cells - Wang, Zheng (Landes Bioscience, 2014)
Elimination of uniparental chromosomes occurs frequently in interspecific hybrid cells. For example, human chromosomes are always eliminated during clone formation when human cells are fused with mouse cells. However, the underlying mechanisms are still elusive. Here, we show that the elimination of human chromosomes in human–mouse hybrid cells is accompanied by continued cell division at the presence of DNA damage on human chromosomes. Deficiency in DNA damage repair on human chromosomes occurs after cell fusion. Furthermore, increasing the level of DNA damage on human chromosomes by irradiation accelerates human chromosome loss in hybrid cells. Our results indicate that the elimination of human chromosomes in human–mouse hybrid cells results from unrepaired DNA damage on human chromosomes. We therefore provide a novel mechanism underlying chromosome instability which may facilitate the understanding of carcinogenesis.